An experimental study of drainage properties of fibrillar-structured materials for glaucoma surgery - N. S. Khodzhaev; M. N. Kolomeytsev (Российский офтальмологический журнал, 2018)
Purpose: to study the drainage properties of fibrillar-structured materials under conditions of hydrodynamics which are maximally close to physiological conditions, using the results of a bench experiment.Material and methods. Drainage properties of fibrillary-structured materials have been studied in several bench experiments using an original device that creates conditions of eye hydrodynamics maximally close to physiological conditions. The studied materials were produced by the method of electrospinning, vacuumized and sterilized. The effect of drainage structure density and drainage type (polylactide, copolymer of polylactide and caprolactone, polycaprolactone) on the drainage capacity were evaluated, as well as the stability of their drainage properties.Results. The research revealed considerable drainage properties of all investigated objects. The study of various drainages showed a statistically significant effect of the density of the internal structure and type on the drainage capacity. Also, a nonlinear increase in the filtering capacity with a regular increase in perfusion pressure was revealed. This phenomenon, regarded as adaptive hydrodynamic properties, in addition to reducing the level of the intraocular pressure (IOP), can contribute to smoothing of diurnal fluctuations, thereby enabling the stabilization of visual functions. In the experiment, the optimal structure was determined, which corresponds to the conditions of physiological hydrodynamics of the eye and ensuring the maintenance of intraocular pressure in the low-norm region. Fibrillar structured drains made of polylactide and its copolymer with polycaprolactone with a porosity of 78–84 %, an average fiber diameter of 5–5.7 μm and a pore size of 25.8–29 μm optimally correspond to hydrodynamic conditions maximally close to physiological conditions.Conclusion. Fibrillar-structured materials have significant drainage properties depending on the density of the internal structure and the type of drainage due to threshold activation of additional pores create the conditions, close to the physiological ones, for the regulation of the IOP, and ensure the persistence of visual functions after operations.